2022
DOI: 10.2991/aebmr.k.220701.067
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Utilitarian and Hedonic Value to Traveler Purchase Intention at Singapore Changi Airport International

Abstract: This study aimed at determining and analyzing the effect of utilitarian and hedonic values on the purchase intention of travelers at Changi International Airport, Singapore. This study employed quantitative research methods. The number of samples in this study was 100 people who were travelers at Changi International Airport, Singapore, from January to November 2019. The sampling technique used was simple random sampling. The data were collected through interviews, questionnaires, and observations. The researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…If a brand can present its products creatively, it can increase purchase interest. The results of this study support research conducted by (Yanson et al, 2022) that the utility value variable value test makes a significant and positive contribution to sustainable purchase intentions. The results of this study are also supported by utility theory which was first proposed by Jereny Bentham, where this theory emphasizes the maximization of happiness or practical benefits, which is in accordance with the concept of utility values.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…If a brand can present its products creatively, it can increase purchase interest. The results of this study support research conducted by (Yanson et al, 2022) that the utility value variable value test makes a significant and positive contribution to sustainable purchase intentions. The results of this study are also supported by utility theory which was first proposed by Jereny Bentham, where this theory emphasizes the maximization of happiness or practical benefits, which is in accordance with the concept of utility values.…”
Section: Discussionsupporting
confidence: 85%
“…Utility value refers to the usability and practical benefits that consumers get from a product or service. Yanson et al, (2022) found that utility value contributes positively and significantly to purchase intentions. Individuals tend to make decisions based on an assessment of the utility or practical benefits obtained from purchasing a product or service.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation